The Da Vinci code [compact disc, unabridged] - Brown, Dan, 1964- (Random House Audio, 2006)
When the Louvre's curator is found murdered in a gallery, symbology expert Robert Langdon is called upon to interpret the enigmatic markings around the body. Langdon encounters Sophie Neveu, the curator's niece, and together she and Langdon seek to unlock the mysteries surrounding the millennium-old Catholic sect, Opus Dei.